Замкненість та нормальна розв'язність оператора, породженого виродженим лінійним диференціальним рівнянням зі змінними коефіцієнтами - Жук, С.М. (Нелінійні коливання, 2007)
Для линейного оператора D : W(F)₂ ⊂ L(n)₂ → L(m)₂ × R(m), порожденного дифференциальным уравнением
d/dt Fx (t) − C(t)x = f(t), F x(t₀) = f₀, установлена замкнутость графика, вычислен сопряженный оператор D^∗ : W(F`)₂ ⊂ L(m)₂ × R(m) → L(n)₂ . Для элементов линейных многовидов W(F)₂ ,W(F`)₂ предложен аналог формулы интегрирования по частям. Получен критерий существования псевдорешения операторного уравнения Dx(·) = (f(·), f₀), сформулированы достаточные
условия нормальной разрешимости оператора D в терминах соотношений для блоков матрицы C(t). Полученные результаты проиллюстрированы примерами For a linear operator D : W(F)₂ ⊂ L(n)₂ → L(m)₂ × R(m), generated by the differential equation d/dt Fx (t) − C(t)x = f(t), F x(t₀) = f₀, we prove that its graph is closed and we calculate the adjoint operator
D^∗ : W(F`)₂ ⊂ L(m)₂ × R(m) → L(n)₂ . For elements of the linear manifolds W(F`)₂ ⊂ L(m)₂ × R(m) → L(n)₂ , we give an analogue of the
integration by part formula. We find a criterion for existence of a pseudo-solution of the operator equation
Dx(·) = (f(·), f₀), and formulate sufficient conditions for normal solvability of the operator D in terms
of relations between blocks of the matrix C(t). The obtained results are illustrated with examples.